Assessment of health-related quality of life: A systematic review of the psychometric properties of HeartQoL - Suellen Rodrigues de Oliveira Maier; Paolla Algarte-Fernandes; Cezar Augusto da Silva Flores; Ingrid Mikaella Alves Santos Bueno; Renata Cristina de Campos Pereira Silveira; Rosana Aparecida Spadoti Dantas; Carina Aparecida Marosti Dessotte (Scientific Electronic Archives, 2026)
To analyze the evidence of the validity of HeartQoL in studies evaluating patients with heart disease who underwent clinical or surgical treatments. Systematic review of the literature for the analysis of psychometric properties reported from PRISMA. The analyses of the findings were carried out following the recommendations of the Joanna Briggs Institute. The synthesis of the findings revealed the psychometric properties of the HeartQoL in different countries. The two-dimensional model of the questionnaire, initially proposed by the authors, was confirmed in some studies through the verification of structural validity, content validity and convergent construct validity, through correlations, and discriminant validity, through the method of known groups using sociodemographic and clinical data. However, it was possible to highlight that in several adaptation studies, they were restricted to translation and back-translation. Although dimensionality has been fragile in some studies because of the loading of items in two domains, we observed the validity and reliability of the HeartQoL. However, we suggest that HeartQoL be adapted prior to its use in cultures other than its original version so that the analysis of psychometric properties is not impaired.